2014
DOI: 10.3892/ol.2014.2158
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits histone H2B monoubiquitination and downstream gene transcription in human breast cancer cells

Abstract: Metformin, one of the most widely prescribed antihyperglycemic drugs, has recently received increasing attention for its potential effects with regard to cancer prevention and treatment. However, the mechanisms behind the suppression of cancer cell growth by metformin remain far from completely understood. The aim of the present study was to investigate whether metformin could regulate histone modification and its downstream gene transcription, and its potential function in inhibiting breast cancer cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The reduction of ATP synthesis activates AMPK, and activated AMPK inhibits hepatic gluconeogenesis while stimulating muscular glucose uptake [ 29 ]. Many studies have found that metformin inhibits cell proliferation via unique mechanisms in different types of cancer cells [ 3 4 5 6 7 ]. However, the association between metformin (or AMPK) and hepatocellular carcinoma has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of ATP synthesis activates AMPK, and activated AMPK inhibits hepatic gluconeogenesis while stimulating muscular glucose uptake [ 29 ]. Many studies have found that metformin inhibits cell proliferation via unique mechanisms in different types of cancer cells [ 3 4 5 6 7 ]. However, the association between metformin (or AMPK) and hepatocellular carcinoma has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological and preclinical studies have suggested various mechanisms underlying the anticancer activity of metformin in different cancer types [ 3 ]. Previous studies have found diverse anticancer effects of metformin in human lung cancer cells [ 4 ], gastric cancer cells [ 5 ], endometrial cancer cells [ 6 ], breast cancer cells [ 7 ], and other types of cancer cells. These studies suggest that metformin inhibits cell proliferation by unique mechanisms in different types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory studies show that metformin use is associated with cell growth suppression in breast cancer cells, possibly mediated by activation of 5'-adenosine monophosphate-activated protein kinase (AMPK) [5,6]. Observational studies also show that metformin use is associated with a 20-30% lower breast cancer incidence [7][8][9].…”
Section: Introductionmentioning
confidence: 92%
“…As O‐GlcNAcylation is thought to promote histone ubiquitination, they also found reduced ubiquitination at H2BK120. Although this study used a different AMPK activator, metformin has been proven to decrease H2BK120 ubiquitination in breast cancer cells . These studies both associated ubiquitination and O‐GlcNAcylation with increased gene expression, although both modifications have also been associated with gene silencing and linked to a variety of other histone modifications that may alter chromatin structure …”
Section: Metforminmentioning
confidence: 99%